Language acculturation : barriers to social distance & psychological distance for Malay learners in higher learning institutions - `Adlina Abd. Khalil,; Norlaila Saadan,; Ong, Jessica Hai Liaw (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to see the challenges of social and psychological distance among Malay students to learn foreign languages. The self-interest and awareness of students is not the only factor to ponder an engagement in learning a foreign language. At the same time, social distance challenges will occur considering the culture of Malay students thought that foreign languages are not easy to learn and complicated. This study also aiming at the alternative taken by the students in order to improve their learning process in mastering a foreign language. The challenges facing by them is in the aspect of self-confidence, peers who can interact in Arabic and Japanese and facilities provided in the campus. Based on the study and observation, students in public universities receive more of these facilities than students in private universities. The main reason is that a reliable financial injection given by the Ministry of Higher Education will certainly be able to help the public universities in strengthening learning facilities for students. 20 respondents were interviewed and information been analyzed narratively through qualitative techniques. The results came up that the variations in background, which is not from the community group that uses the language is also a challenge for them. As an alternative, students can double practice of communicating with foreign students who using both languages most of the times, as well as the role of social media that displays the story of society and by using it in the plot of the story.